AN INQUIRY INTO THE NATURE OF TIBETAN PROVERBS - Sørensen, Per K.; Erhard, Franz Xaver (Proverbium - Yearbook, 2013)
Proverbial sayings and expressions are extremely popular in Tibetan literature. However, in Tibetan scholarship there is no clear definition of the Tibetan proverb. Indigenous genres such as tampé, pechö, legshé, etc. all approximate the genre of proverbs in one way or another, yet at the same time add features that also contradict the genre definition. The essay explores the notion of tampé and related genres and highlights the importance of a universal definition in order to not only differentiate between closely related genres but also in order to classify entries in the proposed dictionary of Tibetan popular figurative literature.